GANDRUNG SEWU FESTIVAL IN BANYUWANGI FROM 2012 TO 2018 - Ayu Trisna Dewi; Sumarjono Sumarjono; Sugiyanto Sugiyanto (JURNAL HISTORICA, 2019)
Abstract The Gandrung Sewu Festival is a traditional celebration featuring thousands of more Gandrung dancers and performed out on the beach. The purpose of Gandrung Sewu Festival is to preserve regional culture and attract tourists to visit Banyuwangi. The results of the research obtained were that the background of the Sewu Gandrung Festival was established by: (1) socio-cultural factors, in which want to prove that Gandrungâ€™s existence is real in Banyuwangi; (2) political factors, in order to attract tourists coming to Banyuwangi; (3) economic factors, in order to increase Domestic Income of Banyuwangi Regency by introducing Gandrung Sewu Festival. The person in charge of the Gandrung Sewu Festival was originally Paguyuban Pelatih Seni dan Tari Banyuwangi â€œPatih Senawangiâ€ (Association, of Art and Dance Coaches of Banyuwangi), there by all the needs of the Gandrung Sewu Festival were completed by Patih Senawangi and there was no assistance from any party. The cost constraints made Patih Senawangi decide not to perform the Gandrung Sewu Festival in the coming year. Finally in 2014, Gandrung Sewu Festival was taken over by the Banyuwangi Regency Culture and Tourism Office. This aims to facilitate tourisme interests, and encourage tourists to Banyuwangi. Keywords: Gandrung Sewu Festival, Culture, Tourism.